GLOBALIZATION AND ITS IMPACT ON THE AESTHETIC EDUCATION OF YOUNG PEOPLE - Абдуллаходжаев, Ғайрат (Ижтимоий-гуманитар фанларнинг долзарб муаммолари / Актуальные проблемы социально-гуманитарных наук / Actual Problems of Humanities and Social Sciences., 2025)
This article examines the impact of globalization on the aesthetic and spiritual education of young people, as well as the role and place of the media in shaping consciousness as a separate group of society.